Large work function shift of gold induced by a novel perfluorinated azobenzene-based self-assembled monolayer - Crivillers, Núria (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.